CONSUMER CONCERNS ON SMART METER USAGE IN MALAYSIA - Siti Nur Hidayah Malek; Afida Jemat (Acta Informatica Malaysia, 2023)
A smart meter is a device to replace outdated traditional meters to track the usage of electricity in real-time with more accurate measurements of energy consumption. In addition, smart meters are also able to record the time of use in short intervals and can be read remotely by the utility. The replacement of smart meter for all houses are a part of the Malaysian government’s initiatives to monitor energy consumption among Malaysians. On top of its advantages, there are some consumers still concerned over several matters such as an increase in electricity bills, security and privacy on personal data protection, health problems associated with the radio frequency (RF) of smart meters, and reliability of the data storage. This study aims to review the customers’ concerns and to propose recommendations for improving the awareness of smart meters’ benefits. In summary, this paper presents an overview from the customer’s point of view and also how to overcome their concerns regarding the use of smart meters instead of traditional meters.